End‐ischemic machine perfusion reduces bile duct injury in donation after circulatory death rat donor livers independent of the machine perfusion temperature. Issue 10 (October 2015) - Westerkamp, Andrie C.; Mahboub, Paria; Meyer, Sophie L.; Hottenrott, Maximilia; Ottens, Petra J.; Wiersema‐Buist, Janneke; Gouw, Annette S. H.; Lisman, Ton; Leuvenink, Henri G. D.; Porte, Robert J.
<x xml:space="preserve">Abstract</x> A short period of oxygenated machine perfusion (MP) after static cold storage (SCS) may reduce biliary injury in donation after cardiac death (DCD) donor livers. However, the ideal perfusion temperature for protection of the bile ducts is unknown. In this study, the optimal perfusion temperature for protection of the bile ducts was assessed. DCD rat livers were preserved by SCS for 6 hours. Thereafter, 1 hour of oxygenated MP was performed using either hypothermic machine perfusion, subnormothermic machine perfusion, or with controlled oxygenated rewarming (COR) conditions. Subsequently, graft and bile duct viability were assessed during 2 hours of normothermic ex situ reperfusion. In the MP study groups, lower levels of transaminases, lactate dehydrogenase (LDH), and thiobarbituric acid reactive substances were measured compared to SCS. In parallel, mitochondrial oxygen consumption and adenosine triphosphate (ATP) production were significantly higher in the MP groups. Biomarkers of biliary function, including bile production, biliary bicarbonate concentration, and pH, were significantly higher in the MP groups, whereas biomarkers of biliary epithelial injury (biliary gamma‐glutamyltransferase [GGT] and LDH), were significantly lower in MP preserved livers. Histological analysis revealed less injury of large bile duct epithelium in the MP groups compared to SCS. In conclusion, compared to SCS, end‐ischemic oxygenated MP of DCD livers provides better preservation of biliary epithelial function and morphology, independent of the temperature at which MP is performed. End‐ischemic oxygenated MP could reduce biliary injury after DCD liver transplantation. Liver Transpl 21:1300‐1311, 2015. © 2015 AASLD.